2012
DOI: 10.1007/s00267-012-9986-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and Phytoplankton Analysis of a Mediterranean Coastal Area

Abstract: 1Identifying and quantifying the key anthropogenic nutrient input sources is essential to adopting 2 management measures that can target input for maximum effect in controlling the phytoplankton biomass. 3In this study three systems characterized by distinctive main nutrient sources were sampled along a 4 Mediterranean coast transect. These sources were: groundwater discharge in the Ahuir area, Serpis River 5 discharge in the Venecia area and a submarine wastewater outfall 1900 m from the coast. The study area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…According to our literature survey, HPLC-CHEMTAX results were not throughly compared with carbon biomass of phytoplankton groups in the Mediterranean Sea with a time series investigation. Previous studies focuses on impact of nutrients on phytoplankton composition and abundance mainly based on CHEMTAX results disregarding phytoplankton carbon biomass [24, 65, 66, 67]. Our results show that CHEMTAX assigned phytoplankton groups should not be assumed as a proxy to abundance or carbon biomass of diatoms, dinoflagellates and haptophytes in the study region located in the northeastern Mediterranean coast.…”
Section: Discussionmentioning
confidence: 63%
“…According to our literature survey, HPLC-CHEMTAX results were not throughly compared with carbon biomass of phytoplankton groups in the Mediterranean Sea with a time series investigation. Previous studies focuses on impact of nutrients on phytoplankton composition and abundance mainly based on CHEMTAX results disregarding phytoplankton carbon biomass [24, 65, 66, 67]. Our results show that CHEMTAX assigned phytoplankton groups should not be assumed as a proxy to abundance or carbon biomass of diatoms, dinoflagellates and haptophytes in the study region located in the northeastern Mediterranean coast.…”
Section: Discussionmentioning
confidence: 63%
“…The DSi concentration in all tanks were lower than that in raw water (Table 1). Studies found that groundwater is characterized by high silica content, because of the lixiviation of biogenic silica from Gramineae (Sebastia & Rodilla, 2013;Sebastiá et al, 2012;Sospedra et al, 2018). The aquaculture water was the mixture of seawater and underground brine in this study.…”
Section: Effects Of Water Quality Parameters On the Phytoplankton Cmentioning
confidence: 83%
“…The decrease or depletion of silica usually causes the decline of diatoms and proliferations of cyanobacteria (Casé et al 2008). In this experiment, the tanks were filled with coastal waters from Gandia Harbor characterized by high silica levels (Sebastiá et al 2012;Sebastiá and Rodilla 2013).…”
Section: Resultsmentioning
confidence: 99%
“…comm. ) to obtain the contribution to total chlorophyll a (Chla) from the phytoplankton and periphyton groups identified with microscopy as described in Sebastiá et al (2012) and Sebastiá and Rodilla (2013). In order to identify groups of samples with similar characteristics, a cluster analysis was performed using STATGRAPHICS Centurion XVI.I to group samples according to pigments concentration.…”
Section: Biological Parametersmentioning
confidence: 99%